2019
DOI: 10.1002/jat.3896
|View full text |Cite
|
Sign up to set email alerts
|

Catalpol protects against 2,3,7,8‐tetrachlorodibenzo‐p‐dioxin‐induced cytotoxicity in osteoblastic MC3T3‐E1 cells

Abstract: 2,3,7,8‐tetrachlorodibenzo‐p‐dioxin (TCDD) is a well‐known environmental contaminant that produces a wide variety of adverse effects in humans. Catalpol, a major bioactive compound enriched in the dried root of Rehmannia glutinosa, is a major iridoid glycoside that alleviates bone loss. However, the detailed mechanisms underlying the effects of catalpol remain unclear. The present study evaluated the effects of catalpol on TCDD‐induced cytotoxicity in osteoblastic MC3T3‐E1 cells. Catalpol inhibited TCDD‐induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
(71 reference statements)
1
5
0
Order By: Relevance
“…CA has been reported to alleviate oxidative stress through upregulation of antioxidant enzymes in animal models of diabetes. , The current study revealed that CA partially suppressed the upregulation of ROS levels in MC3T3-E1 cells on the surface of titanium plates under HGHL conditions, subsequently leading to enhanced osteogenesis of MC3T3-E1 cells (Figure ). Consistent with our findings, Choi et al demonstrated that CA had the potential to mitigate the toxicity induced by 2,3,7,8-tetrachlorodibenzo-p-dioxin in MC3T3-E1 cells due to its antioxidant properties . These findings led us to hypothesize that CA partially abrogates the damage caused by HGHL-induced oxidative stress in osteoblasts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…CA has been reported to alleviate oxidative stress through upregulation of antioxidant enzymes in animal models of diabetes. , The current study revealed that CA partially suppressed the upregulation of ROS levels in MC3T3-E1 cells on the surface of titanium plates under HGHL conditions, subsequently leading to enhanced osteogenesis of MC3T3-E1 cells (Figure ). Consistent with our findings, Choi et al demonstrated that CA had the potential to mitigate the toxicity induced by 2,3,7,8-tetrachlorodibenzo-p-dioxin in MC3T3-E1 cells due to its antioxidant properties . These findings led us to hypothesize that CA partially abrogates the damage caused by HGHL-induced oxidative stress in osteoblasts.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our findings, Choi et al demonstrated that CA had the potential to mitigate the toxicity induced by 2,3,7,8-tetrachlorodibenzo-p-dioxin in MC3T3-E1 cells due to its antioxidant properties. 33 These findings led us to hypothesize that CA partially abrogates the damage caused by HGHL-induced oxidative stress in osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Catalpol, an iridoid glycoside isolated from the roots of R. glutinosa, has been reported to display neuroprotective effects (38,39). Previous studies have also demonstrated the cardioprotective and anti-inflammatory properties of catalpol, including apoptosis inhibition, reduced neuronal death and promotion of differentiation (40,41). In a mouse model of lipopolysaccharide-induced acute lung injury, catalpol prevents injury by inhibiting TNF-α, IL-1β and IL-6 expression (42).…”
Section: Discussionmentioning
confidence: 99%
“…Their work was further validated by the study from Cheng et al, which demonstrated that catalpol could enhance the activity of Wnt/β-catenin axis in MC3T3-E1 osteoblasts under high glucose condition [34]. Choi et al also reported that catalpol prevents MC3T3-E1 osteoblasts apoptosis caused by TCDD-induced damage [35]. Lai and his colleagues found that catalpol could alleviate bone loss by mediating the Th1/Th2 cells paradigm [36].…”
Section: Discussionmentioning
confidence: 92%